Retroperitoneal subphrenic abscesses - Larre Borges, Uruguay; Melogno, Silvio; Carrera, Carlos (Cirugía del Uruguay, 1973)
The authors have made a brief compilation of pathological and clinical aspects of subphrenic retroperitoneal abcesses, including two case histories. The paper contains the anatomical review thereof.